ANALISIS STANDARISASI LABORATORIUM BIOLOGI SEKOLAH MENENGAH ATAS (SMA) DI KOTA PONTIANAK (The Analysis of Standardization of Biology Laboratory at Senior High School in Pontianak) - mutiara adilah; Anandita Eka Setiadi; Adi Pasah Kahar (Jurnal Ilmiah Didaktika, 2021)
The laboratory is an important part of biological learning activities. Previous research has shown that biological laboratories in various cities in Indonesia have different facilities, infrastructures, and management. The pre-observation of six senior high schools in Pontianak City has already shown that they have a laboratory, but standards of completeness of facilities, infrastructure utilization, management, and conditions in six high schools have not yet been known. This research aims to describe the standardization of biology laboratory in six senior high schools in Pontianak City. Methods used are qualitative descriptive with the technique of data collection is through observation, polls, interviews, and documentation. The research object is a biology laboratory in six senior high schools in Pontianak that has been accredited as A and B. The standardization basis of biological laboratory uses Permendiknas No. 24 years 2007 about facilities and infrastructure, Permendiknas No. 26 years 2008 and No. 16 years 2007 about laboratory management, Kemenkes No. 1405/MENKES/SK/XI/2002 about laboratory conditions, and Permendikbud 004/H/AK/2017 about high school accreditation. The results of the study showed that the biology laboratory at four high schools in Pontianak City is standardized with category B because it meets five provisions, while the other two high schools are not standardized because they have not fulfilled the existing conditions.